Cryptocurrencies as a store of value - Filatova, Victoria; Žamberský, Pavel; Jedlinský, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The thesis examines the nature of cryptocurrency studying its potential to serve as a store of value. The conducted analysis of the cryptocurrency market includes an overview of Bitcoin, altcoins and recent trends of the initial coin offering niche identifying the key indicators of the value of cryptocurrency. As the development of the cryptocurrency market attracts not only professional traders but also individual investors, the thesis contains a set of investment portfolios that can be appropriate for them with different levels of returns and risks. However, the cryptocurrency market is still maturing and common approaches can not be applied in all of the cases and different market conditions. That is why each investor has to conduct own continuous analysis and follow the cryptocurrency market trends.
Vedoucí práce: Pavel Žamberský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses